P017 Blue baby blues – a case report; implications of maternal selective serotonin reuptake inhibitor use for sudden infant death syndrome. Issue 7 (19th June 2019) - Mulholland, Peter; Simpson, Alexander; Coutts, Jonathan
Abstract : Background: A baby girl, (38 +2 weeks, 3.026 kg) was admitted on day 3 from home following 2 cyanotic episodes. The pregnancy was uneventful, the mother was prescribed fluoxetine 20mg daily during pregnancy. Investigations: Respiratory studies revealed significant hypoxia in air with episodes of hypoventilation and apnoea. Time spent below 94% saturation was 19%, 68 dips per hour >4%, pCO2 was raised at 7 kPa. She had a normal cranial MRI. Genetic testing for PHOX2B polyalanine expansion mutation was normal excluding Congenital Central Hypoventilation Syndrome (CCHS). Outcome: Incremental increase in the prescription of low flow oxygen normalised her saturation study. She was discharged home on day 14 with an oxygen prescription for 0.5lpm and an apnoea monitor. Parents and family members were taught basic life support. Clinic follow up at 5 months shows baby is thriving, developing normally and the oxygen flow rate has been reduced to 0.3lpm following repeat saturation studies. Discussion: Hypoventilation is not a recognised complication of maternal fluoxetine usage. A population based health registry study found exposure to SSRI in utero increased the rate of neonatal deaths, 1 although a causal relationship could not be established. Two separate randomised controlled trials have looked at the relationship between maternal SSRI use and neonatal death. 2 3 Neither demonstrated a statistically significant correlation, although both showed odds ratios approaching statistical significance (95% confidence intervals 0.82–1.99 and 0.97–3.94 respectively). Mouse models demonstrate the respiratory response to acidosis is abolished by drugs targeting the serotonergic system. 4 This system is not the primary regulator of respiration, 4 and there may be a multi-factorial aetiology to any link between SSRI exposure in utero and the development of hypoventilation. This hypothesis somewhat correlates with the 'triple-risk model' for Sudden Unexpected Death in Infancy (SUDI), which describes three important risk factors; a critical development period, an exogenous stressor and an underlying vulnerability. It is possible that this underlying vulnerability could potentially be accounted for by down-regulation of the serotonergic respiratory response in association with maternal fluoxetine use. Fluoxetine is the preferred SSRI for use in pregnancy. Our case has shown significant hypoventilation in an otherwise healthy infant exposed to maternal fluoxetine in utero with no primary cause identified. This potential correlation should be considered when advising mothers on safe drug use and in the management of neonatal hypoventilation. References: Colvin L, et al. Early morbidity and mortality following in utero exposure to selective serotonin reuptake inhibitors: a population-based study in Western Australia. CNS Drugs . 2012;26:e1–14. Jimenez-Solem E, Andersen JT, Petersen M, Broedbaek K, Lander AR, Afzal SA, Torp-Pedersen C, Poulsen HE. SSRI Use During Pregnancy and Risk of Stillbirth and Neonatal Mortality. American Journal of Psychiatry 2013;170:3. 299–304. WuWen S, Yang Q, Garner P, Fraser W, Olatunbosun O, Nimrod C, Walker M. Selective serotonin reuptake inhibitors and adverse pregnancy outcomes. American Journal of Obstetrics and Gynaecology . 2006. 194: 4. 961–966. Voituron N, et al . Fluoxetine Treatment Abolishes the In Vitro Respiratory Response to Acidosis in Neonatal Mice PLoS One 2010;5(10):e13644.